Use of tusks by narwhals, Monodon monoceros, in foraging, exploratory, and play behavior - Greg O’Corry-Crowe; Maha Ghazal; Mark Gillespie; Paul Galvin; Jason Harasimo; Luke Storrie; Cortney A. Watt (Frontiers in Marine Science, 2025)
Despite the universal fascination with the tusk of the narwhal, the function of this long, spiraled tooth is still debated, primarily because few people have observed how narwhals ( Monodon monoceros ) use their tusks in the wild. Using an unmanned aerial vehicle (UAV), we recorded previously unreported interactions between multiple narwhals, Arctic char ( Salvelinus alpinus ) and glaucous gulls ( Larus hyperboreus ) in Canada’s High Arctic. Narwhals were recorded chasing char and using their tusks to hit, manipulate and influence the behavior of fish. Differences in tusk use likely reflected differences in behavioral intent with some actions associated with prey capture and others with exploration and likely play. Kleptoparasitic behavior by gulls when narwhals pursued char near the surface substantially reduced prey capture for narwhals. Associative and interactive behaviors among narwhals were linked to the ecological context including fish density and gull behavior. Some interactions appeared competitive in nature while others may have been communicative and affiliative. This study revealed that narwhals can use their tusks to investigate and manipulate objects, including prey, and deliver sufficient force with their tusks to stun and possibly kill fish. The speed and agility of char combined with kleptoparasitic behavior of gulls indicate that char may be a challenging species to predate while aspects of the narwhals’ actions may include social learning and exploration of a novel prey species, and are the first reported evidence of likely play, specifically exploratory-object play, in narwhals.